PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTU MEDIA TANGRAM PADA MATERI UNSUR BANGUN DATAR KELAS IV DI SD NEGERI SIDOTOPO I SURABAYA TAHUN PELAJARAN 2024/2025 - Virlyana Meika Damayanti; Lina Listiana; Ihwan Riskya Putra (PROCEEDING UMSURABAYA, 2026)
This study aims to improve students' learning outcomes on the material of flat geometry elements through the application of the problem based learning model assisted by tangram media in class IV of SDN Sidotopo I Surabaya in the 2024/2025 academic year. Based on initial observations, it was found that students' learning outcomes were still low and learning tended to be conventional without concrete media. This study is a classroom based research with a research method by Kemmis and Mc Taggart which was carried out in two cycles with stages of planning, implementation, observation, and reflection. The subjects of the study were 31 students in class IV. Data collection techniques used observation and test at each stage of the cycle. The results of the study showed a significant increase in learning outcomes. The percentage of student learning completion increased from 26% in the pre-cycle, increased to 52% in cycle I, and reached an increase to 81% in cycle II. This increase shows that the application of the problem based learning model assisted by tangram media is effective in improving students' learning outcomes on the material of flat geometry elements. It is suggested that teachers use problem-based learning approaches and concrete media to improve students' participation and understanding of mathematical concepts.